Small-Scale Juicing of Florida-Grown ’UFSun’ Peaches: FSHN23-1/FS451, 12/2023 - Curtis, Savanna J.; Sarkhosh, Ali; Sarnoski, Paul J.; Sims, Charles A.; MacIntosh, Andrew J. (EDIS, 2023)
<!–StartFragment –> Peaches are a promising option for the Florida agricultural industry with plenty of revenue streams including fresh market, U-pick, and retail sales, as well as alternatives in the juicing and fermentation industries. This publication discusses a 2018 case study completed on a Florida peach cultivar. ‘UFSun’ were harvested, processed into juice, and analyzed for sugar content, juice yield, and general economic feasibility. UF/IFAS has bred peach cultivars that grow commercially in tropical and subtropical climates such as Florida’s and are harvest-ready two months before the rest of the United States, offering competitive advantages. Unfortunately, their small size renders them less profitable in fresh markets compared to larger non-Florida cultivars. Knowing the processing characteristics of Florida peaches provides valuable information for peach farmers who are considering using their peaches for juicing, fermentation, and similar purposes.<!–EndFragment –>